Current and Future Prospects for Gene Therapy for Rare Genetic Diseases Affecting the Brain and Spinal Cord - Jensen, Thomas Leth; Gøtzsche, Casper René; Woldbye, David P. D. (Frontiers in Molecular Neuroscience, 2021)
In recent years, gene therapy has been raising hopes towards viable treatment strategy for rare genetic diseases for which there has been almost exclusively supportive treatment. We here review this progress at the preclinical and clinical trial levels as well as market approvals within diseases that specifically affect the brain and spinal cord, including degenerative, developmental, lysosomal storage, and metabolic disorders. The field reached an unprecedented milestone when Zolgensma® (onasemnogene abeparvovec) was approved by the FDA and EMA for in vivo adeno-associated virus-mediated gene replacement therapy for spinal muscular atrophy. Shortly after EMA approved Libmeldy®, an ex vivo gene therapy with lentivirus vector-transduced autologous CD34-positive stem cells, for treatment of metachromatic leukodystrophy. These successes could be the forefront with multiple new gene therapies in development that mostly target loss-of-function mutation diseases with gene replacement (e.g. Batten disease, mucopolysaccharidoses, gangliosidoses) or, less frequently, gain-of-toxic-function mutation diseases by gene therapeutic silencing of pathologic genes (e.g. amyotrophic lateral sclerosis, Huntington’s disease). In addition, the use of genome editing as a gene therapy is being explored for some diseases, but this has so far only reached clinical testing in the treatment of mucopolysaccharidoses. Based on the large number of planned, ongoing, and completed clinical trials for rare genetic central nervous system diseases, it can be expected that several novel gene therapies will be approved and become available within the near future. Essential for this to happen is the in depth characterization of short- and long-term effects, safety aspects, and pharmacodynamics of the applied gene therapy platforms.